What we know and don't know about climate change vulnerability and adaptation in the Inuvialuit Settlement Region (ISR): A systematic review of the literature - Pearce, T; Ford, J; Duerden, F; Smith, Tanya; Andrachuk, M; Smit, B; Westlake, M (ArcticNet Inc., 2009)
This poster presents findings from research that systematically reviewed scientific and grey literature publications addressing climate change vulnerability and adaptation in the Inuvialuit Settlement Region (ISR) in the western Canadian Arctic. The review was structured using a vulnerability approach and 420 documents related directly or indirectly to climate change were analyzed to provide insights on the current state of knowledge on climate change vulnerability in the ISR as a basis for supporting long-term adaptation planning in the region. The literature documents widespread evidence of climate change in the ISR which is compromising food security and health status, limiting transportation access and travel routes to hunting grounds, damaging municipal infrastructure, and affecting the ability to practice traditional cultural activities. Adaptations are being employed to manage changing conditions; however, many of the adaptations being undertaken are short term, ad-hoc, and reactive in nature. Limited long term strategic planning for climate change is being undertaken. Current climate change risks are expected to continue in the future with further implications for communities but less is known about the potential impacts of future climate change and associated adaptive capacity of communities. This review identifi es the importance of targeted vulnerability research that works closely with community members and stakeholders to understand the interaction between current and projected climate change and the social, cultural, economic and demographic factors which condition vulnerability and influence adaptation.